2021
DOI: 10.1108/bfj-01-2021-0023
|View full text |Cite
|
Sign up to set email alerts
|

Non-vegan consumers buying vegan food: the moderating role of conformity

Abstract: PurposeNon-vegan consumers are increasingly shifting their food habits and lifestyles towards vegan food. Thus, in addition to traditional, though poorly studied, ethical motives (i.e. animal, environmental, spiritual, health concerns), other factors may influence the purchase of vegan food. Within this context, the paper investigates the moderating role of conformity in enticing consumers to buy vegan food products, together with the main traditional consumers' concerns influencing their attitude towards vega… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 61 publications
2
28
0
1
Order By: Relevance
“…For instance, we would likely find that animal welfare would be a bigger motivator of vegan food consumption for vegans than for nonvegans. In line with this position, reference [52] shows that spirituality and certain aspects of animal welfare positively influence non-vegan consumers' attitudes and intentions to purchase vegan food but that it is their conformity towards growing trends in vegan food consumption that moderate intentions to purchase. Meanwhile, the comparison in [53] of consumers and non-consumers of legumes (a staple ingredient of the vegan diet) indicated that the latter group was hindered by taste and lack of preparation knowledge and preparation time.…”
Section: Discussionmentioning
confidence: 93%
“…For instance, we would likely find that animal welfare would be a bigger motivator of vegan food consumption for vegans than for nonvegans. In line with this position, reference [52] shows that spirituality and certain aspects of animal welfare positively influence non-vegan consumers' attitudes and intentions to purchase vegan food but that it is their conformity towards growing trends in vegan food consumption that moderate intentions to purchase. Meanwhile, the comparison in [53] of consumers and non-consumers of legumes (a staple ingredient of the vegan diet) indicated that the latter group was hindered by taste and lack of preparation knowledge and preparation time.…”
Section: Discussionmentioning
confidence: 93%
“…It is suggested that restaurants hold strong potential to guide consumers towards more sustainable eating habits (Higgins-Desbiolles and Wijesinghe, 2019; Kim et al, 2020). Despite the impact of veg-friendly restaurants on consumer behaviour and sustainability (Ploll and Stern, 2020;Martinelli and Canio, 2021), little is known about the entrepreneurial journeys of restaurateurs that found them. Moreover, considering that vegan and vegetarian consumers only represent a small portion of the global market, this is an important focal point to better understand how these restaurants emerge.…”
Section: Restaurateurs and Sustainabilitymentioning
confidence: 99%
“…Prior studies have investigated vegans' and nonvegans' attitudes toward vegan foods ( Martinelli & De Canio, 2021 ). According to Cole and Morgan (2011), veganism is sometimes viewed as a deviant practice, and this unfavorable perception is promoted through veganism's misrepresentation.…”
Section: Introductionmentioning
confidence: 99%